Kalmyk Odissey in XX century - Chetyrova, Lyubov B. (The New Research of Tuva, 2011)
This paper is focused on the history of Kalmyk diaspora in the West. The ways of supporting by Kalmyks their ethnic culture is studying.
Keywords: Kalmyks; Diaspora; emigration; West; deportation